Visual Scheme for the Detection of Mobile Attack on WSN Simulator. (6th August 2013) - Jeong, Young-Sik; Kim, Hyun-Woo; Park, Jong Hyuk
Abstract : Recently, wireless sensor networks (WSNs) technologies have been utilized in diverse domains. Areas where WSNs are applied have been expanded from industries, schools, and research institutes to all fields of the human society. However, WSNs should be fixed or flexible depending on the areas of application and monitoring situations. Furthermore, measures for the security of data sensed when sensor nodes communicate with each other are not perfect, so sensors are sometimes easily attacked, and the security measures cover neither cases where sensors receive wrong information nor cases where attacks on external sensor nodes are sensed. Therefore, this paper provides the GML that can be mapped on actual topography so that optimum coverage can be inferred and can set target areas for two situations: mobile sensor networks (MSNs) and fixed sensor networks (FSNs). Sensors can be efficiently arranged through this sensor node information, and when the sensors have been arranged, security simulation functions applied with data encryption for data transmission between sensor nodes are provided. This paper also proposes an external detection trace simulator (EDTS) that would make sensing data transmitted between sensors visually provide information on the sensing of external attacks.